Anaesthetists' accuracy of weight and height estimations in supine adults - Molepo, Shirley Sejabaledi Delina (My University, 2018)
Weight and height estimations have been shown to be inaccurate in clinical practice. Measuring weight and height pre-operatively may pose a challenge and without measurements, anaesthetists make visual estimations without confirmation. The aim of this study was to describe anaesthetists’ accuracy of weight and height estimations in supine adults in the Department of Anaesthesiology at the University of the Witwatersrand. This was a prospective, contextual, descriptive study with six volunteers representing the general population. Sixty-eight consenting anaesthetists were included in the study and data were collected at the two study hospitals. Comparisons were made using Chi2 and one sample t-tests. A total of 408 weight and 408 height estimations were made. Estimations of weight within 10% and height within 5% of the actual values were considered accurate. The overall participants’ accuracy for weight estimation was 40% and 67.6% for height. Weight was overestimated for volunteers with a higher Body Mass Index (BMI) and underestimated for those with lower to normal BMIs. Height was consistently overestimated in shorter and underestimated in taller volunteers. Participants with less than 10 years of clinical experience gave better weight and height estimations than their seniors. There was no association between volunteers and participants’ gender on weight and height estimation. Overall weight and height estimation accuracy was low with height more accurately estimated than weight. Given their extensive application in medicine, actual measurements should be preferred over estimations
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology Johannesburg, 2018